INCREASING PUBLIC KNOWLEDGE REGARDING HEALTHY SANITATION AND DRAINAGE CHANNEL IMPROVEMENT AS A TB PREVENTION STRATEGY - Ika Krisnawati, Dyah; Khafid, Muhamad; Fasya, Abdul Hakim Zakkiy (LPPM Univ. Ibn Khaldun Bogor, 2025)
Poor drainage systems in densely populated areas contribute to increased humidity and the growth of pathogenic microorganisms, which indirectly affect the risk of TB infection. Stagnant water caused by clogged drainage channels can be a source of various infectious diseases, including respiratory infections. Furthermore, unhealthy environmental conditions can weaken the immune system, making people more susceptible to TB infection. In RT 22 RW 02, an investigation revealed that household wastewater disposal is still inadequate. The densely populated area means residents no longer have the space to build infiltration wells for their household wastewater. To dispose of household wastewater, residents channel wastewater into a puddle that lacks a secondary drainage system, resulting in wastewater accumulating there. As can be imagined, this puddle emits an unpleasant odor and can become a breeding ground for mosquitoes and pathogens, seriously threatening residents' health. Even when it rains, water from the puddle overflows onto the road, producing an unpleasant odor. The goal of this community service activity is to increase residents' understanding of healthy environmental sanitation, particularly regarding household wastewater disposal, and to work with residents to improve drainage for household waste disposal. During 3 months, from May-July 2025, the community services of a lecturer from Universitas Nahdlatul Ulama Surabaya (Unusa), together with community self-help, we succeeded in building a 150-meter-long drainage system for disposing of household waste into the nearest river so that there is no more stagnant waste that produces an unpleasant odor.